Applications of surface enhanced Raman scattering (SERS) spectroscopy for detection of nucleic acids - Michałowska Aleksandra; Kudelski Andrzej (Nanophotonics)
Nucleic acids (deoxyribonucleic acid – DNA and ribonucleic acid – RNA) are essential components of all living organisms, with DNA encoding genetic information and RNA facilitating vital biological processes. The detection of nucleic acids having a specific sequence is crucial for identifying organisms and diagnosing genetic diseases. Because surface-enhanced Raman spectroscopy (SERS) is considered as one of the most promising analytical methods that offers important benefits such as short analysis time and exceptional sensitivity compared to other techniques, many groups are trying to apply SERS for nucleic acid detection. This review discusses how SERS spectroscopy can be used for DNA/RNA detection. Beginning with an overview of SERS theory, we delve into various SERS DNA/RNA sensors, including those based on a direct analysis of the SERS spectra of nucleic acids, and many types of sensors based on a selective hybridisation of probe and target nucleic acids. We describe how various types of sensors with increased sensitivity and reliability have evolved (from the first SERS DNA/RNA sensors described in the literature to recently developed ones). Challenges and future directions in SERS sensor development for nucleic acid detection and determination are also discussed. This comprehensive review aims to help researchers understand the field’s nuances, and to foster advancements in the use of SERS spectroscopy in the medical sector.